Easy-to-peel high-resilience low-smoke halogen-free optical cable sheath material and preparation method thereof
By using boron-based silane and O-type silicone sol in optical cable sheath material, combined with polyurethane elastomer and ethylene vinyl acetate, it is solved that the optical cable sheath material in the prior art is difficult to take into account high resilience, easy peelability and low The problem of smoke halogen-free properties achieves high-performance optical cable sheath material.
Patent Information
- Application Number
- CN202411577682.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-07
AI Technical Summary
While the existing optical cable sheath material improves high resilience and easy peeling properties, it is difficult to take into account low smoke and halogen-free properties. The introduction of traditional materials will affect the crosslinking degree and flame retardant properties, resulting in insufficient performance.
Boron-based silane and O-type silicone sol are used as flame retardant release agents, combined with polyurethane elastomer and ethylene vinyl acetate, and through the reaction of ammonium polyphosphate flame retardant and polyurethane prepolymer, a high cross-linking density optical cable sheath material is formed. , enhance its flame retardancy and peelability.
It achieves a balance of high resilience, low smoke halogen-free and easy peeling performance, improves the mechanical properties and flame retardant properties of optical cable sheath material, extends service life and reduces toxic gas emissions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical cable sheath materials, in particular to an easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material and a preparation method thereof. Background Art
[0002] In the communications industry, optical cables are an important medium for transmitting information, and their performance is directly related to the stability and security of communications. Among them, optical cable sheath materials are key materials for protecting optical cables from external influences. They have an important impact on the service life of optical fibers and their shielding layers. At present, the performance trends of optical fiber sheath materials are: first, they need to have high resilience and mechanical properties, so that they can effectively buffer external impacts and other effects, thereby effectively improving protection; second, they need to have easy-to-peel properties, so as to facilitate installation and reduce damage during installation; third, they need to have low smoke and halogen-free properties. Traditional PVC-type sheath materials will produce toxic smoke when burned, which is harmful to the environment and human health.
[0003] In the prior art, elastomers, stripping agents, and flame retardants are usually used to increase the high resilience of optical fiber sheath materials. However, the introduction of elastomers and other substances into general sheath materials reduces compatibility, affects the interface effect and rheological properties, and is not conducive to increasing resilience and mechanical properties. On the other hand, despite the introduction of flame retardants, the flame retardant properties cannot be maximized due to the reduced crosslinking degree.
[0004] In summary, it is of great significance to solve the above problems and prepare a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience. Summary of the invention
[0005] The object of the present invention is to provide a low-smoke halogen-free optical cable sheath material which is easy to strip and has high resilience, and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience, comprising the following steps:
[0008] Step 1: (1) dissolving boric acid in isopropanol, adding vinyl triethoxysilane and 3-aminopropyl triethoxysilane, stirring at room temperature for 8 to 10 hours; adjusting pH to 8 to 10, continuing stirring for 0.5 to 1.5 hours, filtering, washing, and drying to obtain borosilane; (2) adding O-type silica sol to 20 to 30 wt% ethanol aqueous solution, stirring evenly, adding borosilane, heating to 60 to 65° C., stirring for 6 to 8 hours, and drying to obtain a flame retardant stripping agent;
[0009] Step 2: Add ammonium polyphosphate flame retardant, polyurethane prepolymer and catalyst to tetrahydrofuran in sequence, raise the temperature to 70-90° C. and stir for 1.5-2.5 hours; evaporate the solvent at 45-50° C. to obtain a polyurethane elastomer;
[0010] Step 3: Evenly mix low-density polyethylene, ethylene vinyl acetate, polyurethane elastomer, flame retardant stripping agent, compatibilizer and antioxidant, and melt extrude to obtain masterbatch; refine and sheet the masterbatch to obtain low-smoke halogen-free optical cable sheath material.
[0011] More optimally, the raw materials of the low-smoke halogen-free optical cable sheath material include the following components: by weight, 42 to 45 parts of low-density polyethylene, 5 to 8 parts of ethylene vinyl acetate, 28 to 32 parts of polyurethane elastomer, 10 to 13 parts of flame retardant stripping agent, 8 to 9 parts of compatibilizer, and 0.5 to 1 part of antioxidant.
[0012] More optimally, the melt extrusion temperature is 140-150°C, the rotation speed is 150-200rpm; the refining temperature is 130-140°C; the tableting temperature is 160-170°C, the pressure is 15-18Mpa, and the tableting time is 5-10min.
[0013] More optimally, the raw materials of the borosilane include the following components: by weight, 4.5 to 5.5 parts of boric acid, 120 to 150 parts of isopropanol, 4 to 6 parts of vinyl triethoxysilane, and 8 to 10 parts of 3-aminopropyl triethoxysilane;
[0014] The raw materials of the flame retardant stripping agent include O-type silica sol and borosilane in a mass ratio of 1:0.03-0.05, and the solid content of the O-type silica sol is 20-22wt%.
[0015] More optimally, in the raw materials of the polyurethane elastomer, the ammonium polyphosphate flame retardant accounts for 8-10wt% of the mass of the polyurethane prepolymer.
[0016] More optimally, the preparation method of the ammonium polyphosphate flame retardant is as follows: (1) under a nitrogen atmosphere, ammonium polyphosphate and polyethyleneimine are sequentially added to a 95-98wt% ethanol aqueous solution, heated to 75-80°C and stirred for 4-6 hours, filtered and dried to obtain an intermediate product; (2) Tri-buffer solution is added to a 90-92wt% ethanol aqueous solution at a concentration of 0.2-0.3g / mL; sodium hydroxide solution is used to adjust the pH to 8-9; tannic acid and hydrogen peroxide are added and stirred evenly, the intermediate product is added, stirred at 30-35°C for 5-6 hours, filtered and dried to obtain the ammonium polyphosphate flame retardant.
[0017] More optimally, the raw materials of the ammonium polyphosphate flame retardant include the following components: by weight, 10 parts of ammonium polyphosphate, 5 to 7 parts of polyethyleneimine, 8 to 10 parts of tannic acid, and 0.2 to 0.3 parts of hydrogen peroxide.
[0018] More optimally, the compatibilizer includes polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride in a mass ratio of 1.2-1.5:0.5-0.8.
[0019] More optimally, the preparation method of the polyethylene-polyurethane-polyethylene is as follows: (1) low-density polyethylene and 2-mercaptoethanol in a mass ratio of 1:1.1-1.2 are sequentially added to toluene, initiator AIBN is added, the temperature is raised to 105-110°C and stirred for 5-6 hours, washed and dried to obtain hydroxylated polyethylene; (2) hydroxylated polyethylene and polyurethane prepolymer in a mass ratio of 1:2-3 are sequentially added to toluene, a catalyst is added, stirred at 100-105°C for 1-2 hours, washed and dried to obtain polyethylene-polyurethane-polyethylene.
[0020] More optimally, a method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience is provided to prepare a low-smoke halogen-free optical cable sheath material.
[0021] Compared with the prior art, the present application has the following beneficial effects:
[0022] In the scheme, elastomers are introduced to improve the rebound performance; among them, ethylene vinyl acetate is a material with rebound performance, but it has high adhesion, and introducing too much will increase the stripping performance. Therefore, the scheme uses polyurethane elastomers with high strength and high toughness as the main elastic material. The introduction of polyurethane can increase the cross-linking density of the optical cable sheath material, thereby increasing cohesion, effectively improving mechanical properties such as rebound, and ensuring easy stripping performance. On the other hand, the combination of polyurethane and ethylene vinyl acetate allows the optical cable sheath material to maintain softness, enhance mechanical properties such as impact resistance, improve environmental stress cracking resistance, and increase the long-term stability and reliability of optical cable applications in different environments.
[0023] In the scheme, the polyurethane elastomer is prepared by reacting ammonium polyphosphate flame retardant and polyurethane prepolymer E95C; and the ammonium polyphosphate flame retardant is pre-coated with polyethyleneimine and tannic acid to form an intumescent flame retardant. Compared with the direct introduction of ammonium polyphosphate, the increase in residual carbon content and carbon intensity during pyrolysis after coating effectively inhibits the emission of toxic and harmful gases, forming a thermal barrier, thereby effectively improving flame retardancy and low smoke performance. At the same time, the coating effectively improves the composite interface between it and the polyurethane elastomer and enhances its dispersibility in the optical cable sheath material.
[0024] In the scheme, in order to improve the easy stripping performance and further increase the flame retardant performance, the silicon dioxide in the O-type silica sol is used as an inorganic anti-adhesive agent, and the surface is modified by boron-containing borosilane to reduce the force between the sheath material and the optical fiber, which serves as an organic anti-adhesive agent, thereby effectively improving the easy stripping performance. On the other hand, silicon dioxide and boron elements can effectively improve the flame retardancy, and can also reduce the smoke emission of the material during the pyrolysis process, thereby improving the low smoke performance. At the same time, borosilane can also improve its dispersibility in the optical cable sheath material, and a small amount of vinyl silane coupling agent is introduced into the borosilane; it can be partially cross-linked in the optical cable sheath material and the surface, improving durability.
[0025] In the scheme, since the polyurethane elastomer contains ammonium polyphosphate flame retardant, the elastic properties of the polyurethane elastomer will be weakened, so ethylene vinyl acetate is used to cooperate with it to improve the resilience. On the other hand, in the scheme, polyethylene-polyurethane-polyethylene containing polyurethane segments is prepared to assist in improving elasticity. At the same time, the modified polyethylene-polyurethane-polyethylene is prepared from low-density polyethylene and polyurethane prepolymers. The poly raw materials have excellent similar compatibility, so it acts as a compatibilizer, effectively enhancing the interfacial effect between substances and improving mechanical properties; at the same time, it increases segment entanglement and cross-linking, improves cohesion, and thus enhances easy peeling performance.
[0026] In summary, the present application is mainly based on low-density polyethylene, and improves resilience by introducing ethylene vinyl acetate and polyurethane elastomer; effectively enhances strippability by introducing flame retardant stripping agents; at the same time, by introducing ammonium polyphosphate flame retardant into polyurethane, and cooperating with flame retardant stripping agents to effectively improve the flame retardant properties of optical cable sheath materials; by introducing a compatibilizer including polyethylene-polyurethane-polyethylene, the interfacial effect and cross-linking are effectively improved, thereby effectively maximizing the mechanical properties and flame retardant properties of the optical cable sheath material. DETAILED DESCRIPTION
[0027] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0028] It should be noted that the following parts are parts by mass; the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and illustratively include: the model of low-density polyethylene is 1050B, the brand is DowDuPont; the model of polyethylene grafted with maleic anhydride is E158, the brand is DuPont; the solid content of O-type silica sol is 20wt%; the model of polyurethane prepolymer is E95C, purchased from Shanghai Jiren International; the remaining raw materials are commercially purchased.
[0029] The preparation method of ammonium polyphosphate flame retardant is as follows: (1) under nitrogen atmosphere, 10 parts of ammonium polyphosphate and 6 parts of polyethyleneimine are added to 95wt% ethanol aqueous solution in sequence, the temperature is raised to 80°C and stirred for 5 hours, filtered and dried to obtain an intermediate product; (2) Tri-buffer solution is added to 90wt% ethanol aqueous solution at a concentration of 0.2g / mL; sodium hydroxide solution is used to adjust pH=8.6; 10 parts of tannic acid and 0.25 parts of hydrogen peroxide are added and stirred evenly, the intermediate product is added, stirred at 30°C for 6 hours, filtered and dried to obtain ammonium polyphosphate flame retardant.
[0030] The preparation method of polyethylene-polyurethane-polyethylene is as follows: (1) adding 10 parts of low-density polyethylene and 12 parts of 2-mercaptoethanol to toluene in sequence, adding 0.05 parts of initiator AIBN, heating to 110° C. and stirring for 6 hours, washing and drying to obtain hydroxylated polyethylene; (2) adding 10 parts of hydroxylated polyethylene and 22 parts of polyurethane prepolymer to toluene in sequence, adding 0.02 parts of organic tin catalyst MT9001, stirring at 105° C. for 2 hours, washing and drying to obtain polyethylene-polyurethane-polyethylene.
[0031] Embodiment 1: A method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience, comprising the following steps:
[0032] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0033] Step 2: 0.8 parts of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the temperature is raised to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0034] Step 3: 44 parts of low-density polyethylene, 6 parts of ethylene vinyl acetate, 30 parts of polyurethane elastomer, 11 parts of flame retardant stripping agent, 9 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.4:0.6), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0035] Embodiment 2: A method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience, comprising the following steps:
[0036] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0037] Step 2: 1 part of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the mixture is heated to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0038] Step 3: 42 parts of low-density polyethylene, 8 parts of ethylene vinyl acetate, 28 parts of polyurethane elastomer, 13 parts of flame retardant stripping agent, 9 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.2:0.8), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0039] Embodiment 3: A method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience, comprising the following steps:
[0040] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0041] Step 2: 0.8 parts of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the temperature is raised to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0042] Step 3: 45 parts of low-density polyethylene, 5 parts of ethylene vinyl acetate, 32 parts of polyurethane elastomer, 10 parts of flame retardant stripping agent, 8 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.5:0.5), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0043] Comparative Example 1: Based on Example 1, the preparation of the polyurethane elastomer was adjusted, and the rest was the same as Example 1; the details are as follows:
[0044] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0045] Step 2: 0.8 parts of ammonium polyphosphate, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the mixture is heated to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0046] Step 3: 44 parts of low-density polyethylene, 6 parts of ethylene vinyl acetate, 30 parts of polyurethane elastomer, 11 parts of flame retardant stripping agent, 9 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.4:0.6), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0047] Comparative Example 2: Based on Example 1, the preparation of the flame retardant stripping agent was adjusted, and the rest was the same as Example 1; the details are as follows:
[0048] Step 1: Add 10 parts of O-type silica sol to a 20wt% ethanol aqueous solution and stir evenly, add 0.4 parts of 3-aminopropyltriethoxysilane, heat to 60°C, stir for 6 hours, and dry to obtain a flame retardant stripping agent;
[0049] Step 2: 0.8 parts of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the temperature is raised to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0050] Step 3: 44 parts of low-density polyethylene, 6 parts of ethylene vinyl acetate, 30 parts of polyurethane elastomer, 11 parts of flame retardant stripping agent, 9 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.4:0.6), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0051] Comparative Example 3: Based on Example 1, the introduction amount of ethylene vinyl acetate and polyurethane elastic was adjusted, and the rest was the same as Example 1; the details are as follows:
[0052] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0053] Step 2: 0.8 parts of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the temperature is raised to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0054] Step 3: 44 parts of low-density polyethylene, 11 parts of ethylene vinyl acetate, 25 parts of polyurethane elastomer, 11 parts of flame retardant stripping agent, 9 parts of compatibilizer (polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride with a mass ratio of 1.4:0.6), and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt-extruded at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0055] Comparative Example 4: Based on Example 1, only polyethylene grafted with maleic anhydride was used, and the rest was the same as Example 1; the details are as follows:
[0056] Step 1: (1) dissolving 5 parts of boric acid in 150 parts of isopropanol, adding 5 parts of vinyl triethoxysilane and 10 parts of 3-aminopropyl triethoxysilane, stirring at room temperature for 10 hours; adjusting pH to 9.1, continuing stirring for 1 hour, filtering, washing, and drying to obtain borosilane; (2) adding 10 parts of O-type silica sol to 20wt% ethanol aqueous solution and stirring evenly, adding 0.4 parts of borosilane, heating to 60°C and stirring for 6 hours, and drying to obtain a flame retardant stripping agent;
[0057] Step 2: 0.8 parts of ammonium polyphosphate flame retardant, 10 parts of polyurethane prepolymer E95C, and 0.02 parts of organotin catalyst MT9001 are added to 100 parts of tetrahydrofuran in sequence, and the temperature is raised to 90° C. and stirred for 2 hours; the solvent is evaporated at 45° C. to obtain a polyurethane elastomer;
[0058] Step 3: 44 parts of low-density polyethylene, 6 parts of ethylene vinyl acetate, 30 parts of polyurethane elastomer, 11 parts of flame retardant stripping agent, 9 parts of polyethylene grafted maleic anhydride, and 0.5 parts of antioxidant LOWINOX-CA22 are mixed evenly; the rotation speed is set to 200 rpm, and melt extrusion is performed at 145°C to obtain a masterbatch; the masterbatch is refined at 135°C, and the temperature is set to 170°C and the pressure is 15Mpa for 6 minutes to form a sheet to obtain a low-smoke halogen-free optical cable sheath material.
[0059] Performance test 1: The low-smoke halogen-free optical cable sheath materials in the embodiments and comparative examples were subjected to relevant performance tests: (1) a 75 mm × 4 mm × 1 mm sample was prepared, and the tensile strength was tested at a speed of 100 mm / min using a universal tensile testing machine; (2) a 100 mm × 10 mm × 4 mm sample was prepared, and the limiting oxygen index was tested using an oxygen index meter; (3) the stripping force test was tested using the optical fiber stripping force at a rate of 25 mm / min; (4) the permanent deformation was tested by thermal extension at a temperature of 200°C, a pressure of 0.2 MPa, and a time of 15 minutes, and then the permanent deformation rate after cooling was tested for evaluating the resilience. The obtained data are shown in the following table:
[0060] Spline Tensile strength / Mpa LOI / % Peel force / N Permanent deformation rate after cooling / % Example 1 20.7 32.4 70 4.3 Comparative Example 1 18.0 28.9 72 10.1 Comparative Example 2 18.8 29.5 77 8.7 Comparative Example 3 20.3 30.2 81 5.9 Comparative Example 4 19.1 31.9 74 7.3
[0061] Conclusion: From the data in the above table, it can be seen that the present application prepares a low-smoke halogen-free optical cable sheath material, and while introducing functional substances such as flame retardants, the flame retardancy is enhanced on the basis of effectively ensuring mechanical properties through effective modification methods and component ratio settings. The data of comparative examples 1 to 4 are compared with the data of embodiment 1, which shows that: directly introducing ammonium polyphosphate into polyurethane elastomer affects the interface properties and flame retardant properties, resulting in a decrease in performance; using aminosilane coupling agent to replace macromolecular boron-containing silane causes a decrease in related properties; in addition, the ratio of ethylene vinyl acetate and polyurethane elastomer affects the material interface properties, resulting in a decrease in related properties; and using polyethylene grafted maleic anhydride as a compatibilizer alone causes a decrease in mechanical properties and resilience.
[0062] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-smoke halogen-free optical cable sheath material that is easy to strip and has high resilience, characterized in that: The following steps are involved: Step 1: (1) dissolving boric acid in isopropanol, adding vinyl triethoxysilane and 3-aminopropyl triethoxysilane, stirring at room temperature for 8 to 10 hours; adjusting pH to 8 to 10, continuing stirring for 0.5 to 1.5 hours, filtering, washing, and drying to obtain borosilane; (2) adding O-type silica sol to 20 to 30 wt% ethanol aqueous solution, stirring evenly, adding borosilane, heating to 60 to 65° C., stirring for 6 to 8 hours, and drying to obtain a flame retardant stripping agent; Step 2: Add ammonium polyphosphate flame retardant, polyurethane prepolymer and catalyst to tetrahydrofuran in sequence, raise the temperature to 70-90° C. and stir for 1.5-2.5 hours; evaporate the solvent at 45-50° C. to obtain a polyurethane elastomer; Step 3: Evenly mix low-density polyethylene, ethylene vinyl acetate, polyurethane elastomer, flame retardant stripping agent, compatibilizer and antioxidant, and melt extrude to obtain masterbatch; refine and sheet the masterbatch to obtain low-smoke halogen-free optical cable sheath material.
2. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The raw materials of the low-smoke halogen-free optical cable sheath material include the following components: by weight, 42 to 45 parts of low-density polyethylene, 5 to 8 parts of ethylene vinyl acetate, 28 to 32 parts of polyurethane elastomer, 10 to 13 parts of flame retardant stripping agent, 8 to 9 parts of compatibilizer, and 0.5 to 1 part of antioxidant.
3. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The melt extrusion temperature is 140-150° C., the rotation speed is 150-200 rpm; the refining temperature is 130-140° C.; the tableting temperature is 160-170° C., the pressure is 15-18 MPa, and the tableting time is 5-10 min.
4. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The raw materials of the borosilane include the following components: by weight, 4.5 to 5.5 parts of boric acid, 120 to 150 parts of isopropanol, 4 to 6 parts of vinyl triethoxysilane, and 8 to 10 parts of 3-aminopropyl triethoxysilane; The raw materials of the flame retardant stripping agent include O-type silica sol and borosilane in a mass ratio of 1:0.03-0.05, and the solid content of the O-type silica sol is 20-22wt%.
5. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: In the raw materials of the polyurethane elastomer, the ammonium polyphosphate flame retardant accounts for 8-10wt% of the mass of the polyurethane prepolymer.
6. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The preparation method of the ammonium polyphosphate flame retardant is as follows: (1) in a nitrogen atmosphere, ammonium polyphosphate and polyethyleneimine are sequentially added to a 95-98wt% ethanol aqueous solution, the temperature is raised to 75-80°C, stirred for 4-6 hours, filtered, and dried to obtain an intermediate product; (2) Tri-buffer solution is added to a 90-92wt% ethanol aqueous solution at a concentration of 0.2-0.3g / mL; sodium hydroxide solution is used to adjust the pH to 8-9; tannic acid and hydrogen peroxide are added and stirred evenly, the intermediate product is added, stirred at 30-35°C for 5-6 hours, filtered, and dried to obtain the ammonium polyphosphate flame retardant.
7. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The raw materials of the ammonium polyphosphate flame retardant include the following components: by weight, 10 parts of ammonium polyphosphate, 5 to 7 parts of polyethylene imine, 8 to 10 parts of tannic acid, and 0.2 to 0.3 parts of hydrogen peroxide.
8. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The compatibilizer comprises polyethylene-polyurethane-polyethylene and polyethylene grafted maleic anhydride in a mass ratio of 1.2-1.5:0.5-0.
8.
9. The method for preparing the easy-to-strip, high-rebound low-smoke, halogen-free optical cable sheath material according to claim 1, characterized in that: The preparation method of polyethylene-polyurethane-polyethylene is as follows: (1) adding low-density polyethylene and 2-mercaptoethanol in a mass ratio of 1:1.1-1.2 to toluene in sequence, adding initiator AIBN, heating to 105-110°C and stirring for 5-6 hours, washing and drying to obtain hydroxylated polyethylene; (2) adding hydroxylated polyethylene and polyurethane prepolymer in a mass ratio of 1:2-3 to toluene in sequence, adding a catalyst, stirring at 100-105°C for 1-2 hours, washing and drying to obtain polyethylene-polyurethane-polyethylene.
10. The low-smoke zero-halogen optical cable sheath material prepared by the method for preparing an easy-to-strip and high-resilient low-smoke zero-halogen optical cable sheath material according to claim 1.
Citation Information
Patent Citations
Polyolefin-polyurethane-polyolefin triblock copolymer and preparation method thereof
CN104788638A
Preparation and application of fluorescent polytannic acid nano-dot
CN109810691A
Boron affinity molecular imprinting mesoporous polymer based on Mn-doped ZnS quantum dots as well as preparation method and application of boron affinity molecular imprinting mesoporous polymer
CN111621018A
Polyphenol modified liposome nano system as well as preparation method and application thereof
CN113616812A
Anti-agglomeration ceramic powder and preparation method thereof
CN118637896A
